SISTEM KEAMANAN PINTU KELAS DI SMK KOMPUTAMA MAJENANG - Edy Sahputro, slamet Cahyo (Jurnal Teknologi dan Bisnis, 2022)
The development of computer technology and information systems at this time has experienced a very rapid increase, which is in line with the community’s need for information. Today’s society tends to be fast in following the flow of technological developments demands the availability of fast, precise and accurate information. Every agency, good government and private agencies definitely need an information system that is capable of support its performance to obtain and produce information in a more efficient way effective and efficient. One example of technology that is currently developing is system technology security. At SMK Komputama Majenang itself already has CCTV at several points and security as a form of security in schools. But the security system at SMK Komputama Majenang still cannot be said to be strong. Because if you only rely on security, the room security itself is far from several rooms that are considered vital. From the problems that occurred, then the author can provide a solution to the need for a tool that can work simply yet effective for meeting the human need for room security monitors and the need for a tool that can provide early warning when a hazard occurs crime. Based on the discussion that has been carried out in the previous chapters, it can be Several conclusions were drawn, namely with this security system it can prevent actions crime early, with the existence of a magnetic sensor-based door security system.